Risk communication on COVID-19 in South America: An analysis of governmental websites - Pinto, Pâmela Araujo; Ivonete da Silva, Lopes; Daniela de Ulysséa, Leal (Revista Española de Comunicación en Salud, 2023)
Introduction: America was the epicenter for COVID-19, suffering from 44.5% of people infected and 47.4% of deaths. Brazil, Argentina, Colombia, Peru, and Chile are among the most affected countries. Objectives: This article has chosen these countries to analyze how the risks of COVID-19 have been communicated by governments websites to citizens. Methodology: It adopted an exploratory research method with a qualitative approach to describe and evaluate the quality of government information in three dimensions: technical, content and citizen empowerment. Results: From the risk communication perspective, this research identified the inadequacy of the messages on official web pages to the most vulnerable groups and their social specificities. This paper also highlights the absence of accessibility on the contents; the shortage of digital services to serve the population. Conclusion: Government content on COVID-19 requires a dedicated website to facilitate access and guarantee citizens' right to information.
Keywords: health communication; risk communication; COVID-19; public information; South America; access to information